Cerebroprotective effect of pterostilbene against global cerebral ischemia in rats. Issue 5 (May 2021) - Khan, Mohd Muazzam; Badruddeen,; Ahmad, Usama; Akhtar, Juber; Khan, Mohammad Irfan; Khan, Mohd Faiyaz
Abstract: Aim of the study: The role of pterostilbene against induced neurobehavioral alterations in global cerebral ischemia-reperfusion and oxidative damage was studied. Materials and methods: Male SD rats (180–200 g) were exposed for 30 min to bilateral carotid artery occlusion accompanied by 60 min reperfusion to cause cerebral injury. Pretreatment with pterostilbene (200 and 400 mg/kg, orally) was given to the animals for ten days followed by ischemia-reperfusion injury. Various behavioral tests (locomotor activity, neurological score, transfer latency, hanging wire test) were studied. The brain tissues of animals were used for both the biochemical parameters (lipid peroxidation, reduced glutathione, superoxide dismutase, catalase activity) and histopathological study. Result: The pterostilbene as given orally significantly improved neurobehavioral alterations compared to control ischemia-reperfusion. Treatment with pterostilbene (200, and 400 mg/kg, orally) also significantly attenuated oxidative damage as indicated by reduced lipid peroxidation, nitrite concentration, restored reduced glutathione, and catalase activity as compared to control (ischemia-reperfusion) animals. Overall, pterostilbene treated animals showed non significant histological alteration as compared to ischemia-reperfusion control. Conclusion: This work suggests the beneficial effect of pterostilbene and its therapeutic potential against reperfusion-induced ischemia and associated behavioral changes in rats due to the stabilization of DNA damage with significant free radical scavenging properties. Abstract : Pterostilbene, global cerebral ischemia, neurobehavioral alterations.